Pengaruh Literasi Keuangan dan Inklusi Keuangan Terhadap Kinerja UMKM di Kabupaten Bandung - Purnama, Sucia; Susilawati, Susilawati (Jurnal Riset Rumpun Ilmu Ekonomi, 2025)
MSMEs are important for the Indonesian economy, but financial management and access to formal financial services are still problematic. This study examines the influence of financial literacy and inclusion on MSMEs in Bandung Regency. This study is quantitative and survey-based. Non-probability sampling selected 100 MSME actors for this study. The results of this study are that financial literacy affects MSME performance, financial inclusion affects MSME performance, and financial literacy and inclusion affect MSME performance.